2021
DOI: 10.1101/2021.10.15.464616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatocyte Cell Cycle Progression Depends on a Transcriptional Repressor Cascade Downstream of Wnt Signaling

Abstract: Cell proliferation is tightly controlled by inhibitors that block cell cycle progression until growth signals relieve this inhibition. In several tissues including the liver, transcriptional repressors such as E2F7 and E2F8 function as inhibitors of mitosis and promote polyploidy, but how growth factors release these mitotic inhibitors to facilitate cell cycle progression is unknown. We describe here a newly identified mechanism of cell division control in which Wnt/βcatenin signaling in the postnatal liver ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that Tbx3 regulates division of hepatoblasts during embryonic liver development by repressing cell cycle inhibitors (Suzuki et al 2008). In an accompanying manuscript, we show that Tbx3 is required for hepatocyte cell division during postnatal development (Jin et al 2021). To determine if Tbx3 plays a role in IF-induced hepatocyte proliferation, we genetically depleted Tbx3 in hepatocytes and traced expansion of Axin2+ GFP-labeled cells after .…”
Section: Endocrine Fgf15-b-klotho Signaling Is Required For Hepatocyte Proliferation During Intermittent Fastingmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous studies have demonstrated that Tbx3 regulates division of hepatoblasts during embryonic liver development by repressing cell cycle inhibitors (Suzuki et al 2008). In an accompanying manuscript, we show that Tbx3 is required for hepatocyte cell division during postnatal development (Jin et al 2021). To determine if Tbx3 plays a role in IF-induced hepatocyte proliferation, we genetically depleted Tbx3 in hepatocytes and traced expansion of Axin2+ GFP-labeled cells after .…”
Section: Endocrine Fgf15-b-klotho Signaling Is Required For Hepatocyte Proliferation During Intermittent Fastingmentioning
confidence: 52%
“…Pericentral hepatocyte proliferation ensures replacement of lost cellular mass through increases in overall cell numbers. Together with the work in an accompanying paper (Jin et al 2021) we propose our current working model in which paracrine WNT and endocrine FGF pathways work together to push hepatocytes through different phases of the cell cycle. Specifically, the general role of FGF in cell proliferation observed in our studies suggest that this signal initiates S-phase, whereas WNT through TBX3 permits progression through Mphase by repressing cell division inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent these challenges, we sought to specifically measure RB protein concentrations in proliferating isolated primary hepatocytes. To do this, we used a 2D primary hepatocyte culture protocol 31,32 (Figure 3A). In these cultures, primary hepatocytes actively enter the cell cycle, and we can detect RB protein using immunfluorescence because the autofluorescence is significantly reduced in the isolated hepatocytes compared to those in the mouse liver (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…The protocol for 2D culture of primary hepatocytes was kindly shared by Yinhua Jin from Dr. Roeland Nusse's lab at Stanford University 31,32 . Briefly, primary hepatocytes from Rb1 flx/flx ; Rosa26-CreER2; Fucci2 mouse were isolated by two-step collagenase perfusion.…”
Section: Primary Hepatocyte 2d Culturementioning
confidence: 99%
“…To circumvent these challenges, we sought to specifically measure RB protein concentrations in proliferating isolated primary hepatocytes. To do this, we used a 2D primary hepatocyte culture protocol ( Peng et al, 2018 ; Jin et al, 2021 ) ( Figure 3A ). In these cultures, primary hepatocytes actively enter the cell cycle, and we can detect RB protein using immunfluorescence because the autofluorescence is significantly reduced in the isolated hepatocytes compared to those in the mouse liver.…”
Section: Resultsmentioning
confidence: 99%